2019
DOI: 10.1002/ecs2.2958
|View full text |Cite
|
Sign up to set email alerts
|

Riparian soil nitrogen cycling and isotopic enrichment in response to a long‐term salmon carcass manipulation experiment

Abstract: Pacific salmon acquire most of their biomass in the ocean before returning to spawn and die in coastal streams and lakes, thus providing subsidies of marine-derived nitrogen (MDN) to freshwater and terrestrial ecosystems. Recent declines in salmon abundance have raised questions of whether managers should mitigate for losses of salmon MDN subsidies. To test the long-term importance of salmon subsidies to riparian ecosystems, we measured soil nitrogen cycling in response to a 20-yr manipulation where salmon car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 74 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…Continued) v www.esajournals.org have rhizomes as long as 5 to 18 m, depending on the forest type (Tappeiner et al 1991). Furthermore, previous research has demonstrated that nutrient availability in riparian areas can be highly variable within a watershed, regardless of the presence of salmon-derived nutrients (Feddern et al 2019). In salmon-bearing streams, bears are primary drivers of changes in nutrient cycling, while adding to the spatial inequality of carcass deposition (Holtgrieve et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Continued) v www.esajournals.org have rhizomes as long as 5 to 18 m, depending on the forest type (Tappeiner et al 1991). Furthermore, previous research has demonstrated that nutrient availability in riparian areas can be highly variable within a watershed, regardless of the presence of salmon-derived nutrients (Feddern et al 2019). In salmon-bearing streams, bears are primary drivers of changes in nutrient cycling, while adding to the spatial inequality of carcass deposition (Holtgrieve et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2002, Feddern et al. 2019). In the southern distribution of Pacific salmon in North America, most salmon populations spawn in the late summer or early fall, near the end of the active growing season.…”
Section: Discussionmentioning
confidence: 99%
“…2011, Feddern et al. 2019). In general, additions of nitrogen fertilizer increase the availability and accumulation of nitrogen in soils, but concurrent increases in rates of nitrogen emission and leaching limit the benefits of fertilization to plant uptake over time (Lu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations